Literature review: technological interventions and their impact on quality of life for people living with dementia - David Sanders; Philip Scott (BMJ Health & Care Informatics)
Objectives Rapid technology-driven innovation in the healthcare sector has led to an increasing ability to effectively respond to health challenges. However, the cognitive challenges faced by a person with dementia exacerbate the difficulty of designing enduring technological dementia care solutions. Despite this, and in the absence of a cure, facilitating well-being and improved quality of life becomes pivotal for those living with dementia and their caregivers. This review aimed to identify and consolidate the provision of technological solutions for dementia care, and how these are perceived to impact the quality of life of a person with dementia.Methods Articles and journals were identified using keywords including those relating to quality of life, assistive technologies and technology adoption and acceptance. Greater priority was given to resources published after 2010 due to the speed of technological advancement, and peer-reviewed articles were preferred.Results 91 resources were identified, with 38 contributing to the final review. In addition to multiple quality of life measurement tools, the literature identified a large variety of solutions that fell into three categories: those used ‘by’, ‘with’ or ‘on’ a person with dementia.Conclusions This review concludes that the ‘one size fits all’ approach to many solutions reflects the lack of supporting evidence, negatively impacting trust in their usefulness among caregivers and their subsequent adoption rates. This could be attributed to limited involvement of people with dementia in studies of effectiveness and adoption. Additional research is recommended to further consolidate research on quality of life and to understand the individuality and progression of dementia and its influence on dementia care solutions.